(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
This paper is based on a phenomenological investigation regarding the subjective experience of the awareness of finitude during old-age. Three elders who had already undergone the awareness of finitude were selected and Amadeo Giorgi’s method was used in order to describe this lived experience and its respective acts of meaning. Results revealed the existence of nine key-constituents in its general structure of meaning. Two of them resulted from life events which originated the emergency of this particular awareness (unexpected loss of significant reference; body and temporal limits), while the other seven (memory of relational separation; anticipation; paradoxical situation; uncertainty; spiritual questioning; emotional vulnerability; change of perspective and r elatedness with existence), were key constituents that were built without being directly related to life and/or ageing contingencies. Subsequently, these findings where contextualized within a phenomenological-existential background, allowing the acknowledgement of how this respective awareness and its subjective meaning seem very much undermined by the elder’s temporality, corporality, historicity and relatedness, and play in the end a fundamental role that will significantly set the way in which elders deal with their remaining time.